The effect of correlation between a spring wheat variety with soil tillage technologies and doses of nitrogen fertilizers on the interannual yield stability - А. А. Konitshev; I. I. Garifullin (Зерновое хозяйство России)
There was studied the possibility of reducing the effect of weather conditions on spring wheat productivity in the Non-Blackearth zone due to improving tillage technologies. There has been established that on soddy-podzolic light loamy soil, on the fields of the Ivanovsky Research Institute of Agriculture in the period 2013–2019, the difference in the number of productive stems per m2 when using plowing or minimal tillage was not significant when the HTC changed from 0.73 to 2.65, except the year of 2017 (HTC = 2.19), when there was increased soil moisture throughout the vegetation period. The advantage of minimal tillage under these conditions was 30 %. According to number of kernels per ear, there was identified a significant advantage (more than 20 % (HTC = 2.65; 0.99)) of plowing over minimum tillage (by 13–14 %) during the years with soil moisture in the wheat booting stage. When applying experimental tillage, there have been formed areas with a variable density in the lower part of the arable layer, each of which is favorable for plant development under a certain soil moisture. The transition to experimental tillage has increased number of productive stems on 1–6 %. Number of kernels per ear when using experimental tillage significantly exceeded this indicator (by 5–18 %) under a minimum tillage in the entire range of moisture. Compared to plowing, the advantage of experimental tillage according to number of kernels per ear was 0–27 %. The effect of weather conditions on a number of productive stems was 74.8 %, and number of kernels per ear was 32.4 %. The effect of mineral fertilizers on these parameters of the yield structure was 1.8 and 26.2 %, respectively.